A Comparative Study of Regional Cerebral Blood Flow Asymmetry Index in Stroke Patients with or without Poststroke Depression Using 99mTc-ECD Single-Photon Emission Computed Tomography - Pradeep Kumar Maurya; Abdul Qavi; Satyawati Deswal; Ajai Kumar Singh; Dinkar Kulshreshtha; Anup Kumar Thacker (World Journal of Nuclear Medicine)
Introduction Stroke is a major cause of death and disability around the globe. The development of depression following a stroke further increases the disability and impairs functional recovery. In recent decades, despite the advancement in structural and nuclear medicine imaging, the pathophysiologic basis of poststroke depression (PSD) is not well understood. Etiopathogenesis of PSD is multifactorial and afflictions of the frontal lobe, hippocampus, limbic region, and basal ganglia projections are implicated. Aim The aim of this study was to assess the regional cerebral blood flow (rCBF) using 99mTc-ethyl cysteinate dimer single-photon emission computed tomography (SPECT) in patients with (PSD + ) or without PSD (PSD–). Materials and Methods To evaluate the hemispheric asymmetry, the percentage of asymmetry index (AI) was calculated for frontal, temporal, parietal, occipital, putamen, caudate, and thalamic regions of brain and compared between PSD+ and PSD–. The correlation between AIs over the different brain regions was also established in patients of PSD+ and PSD–. Our study cohort included 122 patients between 6 weeks and 1 year of stroke. Depression was present in 52 (42.6%) patients, assessed by hospital anxiety and depression scale (HADS) and general health questionnaire-28 items (GHQ-28) scale. The 28 patients with PSD+ and 18 PSD– gave consent for SPECT study. Results Our results are based on 46 patients who underwent SPECT study. In patients with PSD+ and PSD–, the HADS and GHQ-28 scores were 8.93 ± 2.77 vs. 3.94 ± 2.15 (p = 0.001) and 40.96 ± 9.48 vs. 17.72 ± 5.38 (p = 0.001), respectively. A significant difference in rCBF AI was found in the temporal lobe (p = 0.03) between patients of PSD+ and PSD–. On logistic regression analysis, the odds ratio of rCBF AI for temporal lobe was 0.89 (95% confidence interval [CI]: 0.80–0.99; p = 0.04) and caudate nucleus was 0.85 (95% CI: 0.73–0.98; p = 0.03), which were statistically significant. PSD correlated with AI in temporal region (r = –0.03; p = 0.03) but did not show significant correlation with other regions of brain between PSD+ and PSD–. Conclusion The presence of temporal lobe rCBF AI on SPECT is significantly associated with PSD. This may reflect the dysfunction of the limbic system and contribute to the occurrence of PSD.